Analysis and optimization of quantum adaptive measurement protocols with the framework of preparation games - M. Weilenmann (Nature Portfolio, 2021)
Finding a general way to come up with optimal strategies for quantum information tasks is a matter of both fundamental and practical interest. Here, the authors tackle the problem using the formalism of quantum preparation games, finding applications for entanglement detection and quantification.